Generation and photogeneration of hydroxyl radicals and singlet oxygen by particulate matter and its inorganic components. Issue 6 (December 2021) - Mikrut, Magdalena; Mazuryk, Olga; Macyk, Wojciech; van Eldik, Rudi; Stochel, Grażyna
Abstract: Polluted air containing particulate matter (PM) is a huge environmental problem in the city of Kraków, Poland. PM causes numerous negative health effects including infection of the respiration system and cardiovascular disorders. The development of autoimmune disorders can be facilitated by redox active transition metals due to the generation of reactive oxygen species (ROS) and induction of oxidative stress, which results in lipid peroxidation, protein oxidation and severe oxidative modification of DNA. Our goal was to study ROS generation (in particular, HO and 1 O2 ) in the presence of PM collected via different procedures at different locations in Kraków. Scanning electron microscopy analysis confirmed that in all collected samples, aggregates of small grains could be observed. Cold plasma treatment was used to remove parts of the organic matter and to uncover inorganic compounds which become more relevant following plasma treatment. All samples were photoactive and showed hydroxyl radical generation. Singlet oxygen production studies indicated that during plasma treatment, unsaturated organic species are produced that intensify the generation of 1 O2 . Generation of hydroxyl radicals and singlet oxygen in vitro was confirmed using human epithelial cell line A549. Graphical Abstract: ga1 Highlights: Particulate matter (PM) from Kraków, PL, shows high organic content, over 40% of C. Singlet oxygen and hydroxyl radicals are among ROS (photo)generated at PM. Low temperature oxygen plasma treatment efficiently removes organic carbon. Decreasing content of organics in PM results in diminished ROS production. Production of ROS in lung epithelial cells was confirmed upon contact with PM.